2004
DOI: 10.1038/sj.bjp.0705902
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinomimetic arachidonyl‐2‐chloroethylamide (ACEA) acts on capsaicin‐sensitive TRPV1 receptors but not cannabinoid receptors in rat joints

Abstract: 1 The vasoactive effects of the synthetic cannabinoid (CB) arachidonyl-2-chloroethylamide (ACEA) was tested in the knee joints of urethane-anaesthetised rats. Experiments were also performed to determine whether these vasomotor responses could be blocked by the selective CB 1 receptor antagonists AM251 (N-(piperidin-1-yl)-5-(4-iodophenyl)-1-(2,4-dichlorophenyl)-4-methyl-1H-pyrazole-3-carboxamide) (10 À9 mol) and AM281 (1-(2,4-dichlorophenyl)-5-(4-iodophenyl)-4-methyl-N-4-morpholinyl-1H-pyrazole-3-carboxamide) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 41 publications
(63 reference statements)
2
24
0
Order By: Relevance
“…An interesting aspect of the anandamide study was that its stimulatory effect on joint nociceptors was attained by activating the transient receptor potential (TRP) vanilloid channel 1 (TRPV 1 ). This pathway was reaffirmed by joint blood flow experiments that showed that the vasomotor effects of a selective CB 1 agonist in rat knees could be blocked by TRPV 1 antagonism [87]. Zygmunt and coworkers [88] deduced that anandamide activation of TRPV 1 channels on sensory nerves causes the secondary release of CGRP.…”
Section: Factors Contributing To Joint Peripheral Sensitizationmentioning
confidence: 94%
“…An interesting aspect of the anandamide study was that its stimulatory effect on joint nociceptors was attained by activating the transient receptor potential (TRP) vanilloid channel 1 (TRPV 1 ). This pathway was reaffirmed by joint blood flow experiments that showed that the vasomotor effects of a selective CB 1 agonist in rat knees could be blocked by TRPV 1 antagonism [87]. Zygmunt and coworkers [88] deduced that anandamide activation of TRPV 1 channels on sensory nerves causes the secondary release of CGRP.…”
Section: Factors Contributing To Joint Peripheral Sensitizationmentioning
confidence: 94%
“…5,9,27,28 Evidence is also emerging for the existence of several other pharmacological targets that respond to at least some established cannabinoid receptor agonists or to abnormal-cannabidiol, a synthetic analogue of the plant cannabinoid cannabidiol that lacks significant affinity for both CB 1 and CB 2 receptors. 5,9 These include:…”
Section: 26mentioning
confidence: 99%
“…Thus, the present results provide the first definite evidence for the regulatory role of TRPV1 receptors in the long-term inflammatory and hyperalgesic symptoms of the adjuvant arthritis model. Several mediators, such as bradykinin, prostaglandins, protons, histamine, serotonin, nerve growth factor (Ferrell and Lam, 1996;Szolcsanyi et al, 1998a), and endocannabinoids (Gauldie et al, 2001;Baker and McDougall, 2004) released during arthritis have been shown to activate or sensitize the capsaicin-sensitive nerve endings. TRPV1 activation induces the release of inflammatory neuropeptides such as substance P and CGRP, which evoke local plasma protein extravasation, arteriolar vasodilatation Ferrell, 1991, 1993), and stimulate inflammatory cells in the joint.…”
Section: Role Of Trpv1 In Adjuvant-induced Chronic Murine Arthritis 115mentioning
confidence: 99%